Pembelajaran Sejarah Lokal Gerakan Samin Surosentiko di SMA Negeri 1 Cepu - Naufal Nursyifa Rizki Widodo; Tsabit Azinar Ahmad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Local history learning plays a strategic role in building students' historical awareness and cultural identity, but its formal integration into history lessons at SMA Negeri 1 Cepu has yet to materialize. This study aims to describe the planning, implementation, and evaluation of local history learning, the